Análisis de la demanda hídrica de los cultivos de caña de azúcar, arroz, sandía y melón en la cuenca media y baja de Río Tempisque, mediante el tratamiento e imágenes satelitales en el periodo 1990-2017 - Hernández-Camacho, Magdiel Alejandro (Instituto Tecnológico de Costa Rica, 2018)
In this project, water demand was analyzed by sugarcane, rice, melon and watermelon crops in the middle and lower basins of the Tempisque River, through the processing of satellite images in the 1990-2017 period; The purpose of the study is to compare what was obtained through the analysis with the flow concessioned and supplied by the governmental entities (Water Directorate (DA) and National Service of Groundwater Irrigation and Drainage (SENARA) through the Arenal-Tempisque irrigation district). For this, data was generated through supervised classification with Landsat 5, 7 and 8 images; and, with the areas obtained for agricultural use, the procedure of the manual of endowments of the Water Direction was applied to obtain the water demand of the crops under analysis, and thus be able to compare it with the database of the two government entities. Regarding the results, it was obtained that the flow analyzed is greater than that supplied by the entities, and the environmental impact is positive because the concessions leave a non-concessioned flow greater than the environmental flow, this in April, the most critical of the year, which does not affect the population near the Tempisque River since they can concession water from it.
Proyecto de Graduación (Licenciatura en Ingeniería Agrícola) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Agrícola, 2018
Keywords: Cultivos; Teledetección; Cuencas; Imágenes satelitales; Medidas de caudal